Recent Developments on Gas‐Phase Volatile Organic Compounds Abatement Based on Photocatalysis. Issue 11 (1st September 2022) - Xu, Zhenmin; Ren, Yuqing; Deng, Xiaoming; Xu, Mengli; Chai, Wei; Qian, Xufang; Bian, Zhenfeng
Abstract : The health and environmental problems caused by volatile organic compounds (VOCs) have attracted wide attention. Photocatalytic technology provides a green and sustainable way for VOCs removal. How to build a highly efficient and stable photocatalyst is of great significance to promote the practical application of photocatalysis technology. In this review, the literatures on photocatalytic oxidation in VOCs are surveyed and systematically categorized based on the types of photocatalytic materials. The methods of improving photocatalytic activity are studied, and the deactivation process of photocatalyst is discussed. Finally, the reaction mechanism is summarized according to the charge separation process and the classification of reactive oxygen species. Abstract : The literature about photocatalytic oxidation in volatile organic compounds is surveyed and systematically categorized based on the types of photocatalytic materials. The methods of improving photocatalytic activity are studied, and the deactivation process of photocatalyst is discussed. The reaction mechanism is summarized according to the charge separation process and the classification of reactive oxygen species.